The gut dysbiosis and plasma lipid metabolisms signatures in children with active tuberculosis - Baixu Sun; Xiaoran Yu; Hui Qi; Fang Xu; Weiwei Jiao; Min Fang; Li Duan; Xi Zeng; Xuemei Yang; Xingyun Wang; Yu Zhu; Kaixia Mi; et al. (BMC Microbiology)
Abstract Background The human gut microbiota is an important modulator of host immune responses and has a crucial role in the development of tuberculosis (TB). Evidences suggest that metabolites may function as a bridge between gut microbiome and TB progression in children. However, the underlying interactive mechanisms are not well explored. The results may provide useful insight into the role played by the gut microbiome in pulmonary TB in children. Methods To explore the gut bacterial features and its interaction with plasma lipid metabolisms in children with TB. We enrolled children aged younger than 14 years old from Beijing Children’s Hospital and West China Second Hospital between January 2020 and June 2021. We investigated the gut bacterial community using 16S rRNA sequencing of 98 children with active TB, 37 other infectious diseases, and 80 healthy children. The plasma lipids were further analyzed using ultra-high-performance liquid chromatography coupled with mass spectrometry. Results Children with TB showed decreased diversity and species richness indices compared to healthy children. Significant increases in the abundance of Firmicutes and Actinobacteriota combined with a decrease in the abundance of Bacteroidetes and Proteobacteria were also observed in TB children when compared with healthy controls. Among children with TB, gut bacterial composition differed in subgroups with pulmonary and extrapulmonary TB, or subgroups with different Mycobacterium tuberculosis (MTB) load. Children with TB had a higher risk of fever (OR = 3.02, P = 0.005) and poor appetite (OR = 2.96, P = 0.02) than the controls. Several bacterial genera were associated with severe illness and clinical indices, such as aspartate aminotransferase levels and fever. The plasma lipids showedc difference between TB patients and the children with other infectious diseases. Eight genera with the highest relative abundance strongly correlated with the plasma lipids. Conclusions The gut microbiome is compromised in TB children, with a correlation with the plasma lipid metabolites and clinical presentations. Integrating analysis of microbiome and metabolism may help improve precise diagnosis, treatment, and mechanism study for TB in children.